The Impact of Parent-Child Relationship on the Peer Sociometric Status of High School Students - V.I. Ekimova; A.N. Vetzel; M.I. Rozenova (Культурно-историческая психология, 2022)
The investigations of psychological problems of family relations and their impact on the child and adolescent peer relationship are especially important for high school students who are on the verge of adulthood. The article presents the overview of the Russian and foreign publications, and the results of the empirical study of parent-child relationship impact on the peer sociometric status of high school students. The empirical study involved 106 participants: 53 tenth grade students aged 15 to 16 (M=15,8), including 24 girls and 29 boys, and their mothers (N=53) aged 37 to 43 years old (M=40,4). Methods used: sociometric test (J. Moreno); “Adolescents about Parents Questionnaire” (ADOR/POR); questionnaire for parents “Analysis of family relationships” (AFR). The results obtained allow us to state that high school students with the high sociometric status are less likely to encounter manifestations of directiveness, hostility, and distancing from their parents. It is noted that the low sociometric status of students is largely associated with such disharmony of parenting styles as hypoprotection and abuse.